The Implementation Of Peer Tutorial Method On Three Dimensional Mathematics Lesson In XII IPA 5 Class At SMA Negeri 3 Jember, Odd Semester, In The Academic Year Of 2019/2020 - Teripena E. C (Pancaran Pendidikan, 2019)
We already know that children have got a phobia and make them unable to give the response to math lessons well. It concerns us since mathematics is included in one of the UNBK subjects. This research was intended to improve the students' understanding and motivation so that they understood the concept of the probability of multiple events. In this research, the researchers chose 5 students in a class whose math scores were above the average of the other classmates and they were able to help other friends in understanding mathematical concepts taught by the teacher.       The research was conducted in 2 cycles and 2 meetings. The research subjects covered the XII IPA5 students of 2019/2020 in the odd semester at SMA Negeri 3 Jember. The methods used in this research were observation, interview, and documentation. Based on the results of research and analysis of existing data, it can be concluded that there was a significant increase in the tutors motivation and the activities of peer tutorial participants from cycle I to cycle II. The tutor had a good motivation. Participants' activities in the first cycle reached 70 and 80.8 in the second cycle, which means that the participants of peer tutorials were motivated so that their mean result of learning outcomes improved.